Ventral midline thalamus is not necessary for systemic consolidation of a social memory in the rat. (July 2020) - Quet, Etienne; Cassel, Jean-Christophe; Cosquer, Brigitte; Galloux, Marine; Pereira De Vasconcelos, Anne; Stéphan, Aline
According to the standard theory of memory consolidation, recent memories are stored in the hippocampus before their transfer to cortical modules, a process called systemic consolidation. The ventral midline thalamus (reuniens and rhomboid nuclei, ReRh) takes part in this transfer as its lesion disrupts systemic consolidation of spatial and contextual fear memories. Here, we wondered whether ReRh lesions would also affect the systemic consolidation of another type of memory, namely an olfaction-based social memory. To address this question we focused on social transmission of food preference. Adult Long-Evans rats were subjected to N-methyl-d -aspartate-induced, fibre-sparing lesions of the ReRh nuclei or to a sham-operation, and subsequently trained in a social transmission of food preference paradigm. Retrieval was tested on the next day (recent memory, nSham  = 10, nReRh  = 12) or after a 25-day delay (remote memory, nSham  = 10, nReRh  = 10). All rats, whether sham-operated or subjected to ReRh lesions, learned and remembered the task normally, whatever the delay. Compared to our former results on spatial and contextual fear memories (Ali et al., 2017; Klein et al., 2019; Loureiro et al., 2012; Quet et al., 2020), the present findings indicate that the ReRh nuclei might not be part of a generic, systemic consolidation mechanism processing all kinds of memories in order to make them persistent. The difference between social transmission of food preference and spatial or contextual fear memories could be explained by the fact that social transmission of food preference is not hippocampus-dependent and that the persistence of social transmission of food preference memory relies on different circuits.